Palladium-Catalyzed Synthesis of Benzofuran Spiroketals Derived from Cholesterol; NMR and X-ray Characterization - García-Santos, William H.; Quiroz-Mendoza, Ariadna M.; Mayorquín-Torres, Martha C.; Flores-Álamo, Marcos; Iglesias-Arteaga, Martin A. (Synthesis, 2023)
The synthesis of two diastereomeric steroid spiroketals bearing a 2,3-dihydrobenzofuran moiety is described. The structure of the obtained compounds was elucidated by combined 1D and 2D NMR techniques and corroborated by X-ray crystallography studies.
Keywords: steroids; benzofuran spiroketals; palladium-catalyzed spiroketalization; NMR; X-ray diffraction